MiR‐642a‐5p partially mediates the effects of lipopolysaccharide on human pulmonary microvascular endothelial cells via eEF2. Issue 11 (16th October 2020) - Fei, Liming; Sun, Gengyun; You, Qinghai
Abstract : Inhalation or systemic administration of lipopolysaccharide (LPS) can induce acute pulmonary inflammation and lung injury. The pulmonary vasculature is composed of pulmonary microvascular endothelial cells (PMVECs), which form a semiselective membrane for gas exchange. The miRNA miR‐642a‐5p has previously been reported to be up‐regulated in patients with acute respiratory distress syndrome; thus, here, we examined whether this miRNA is involved in the effects of LPS on PMVECs. The levels of miR‐642a‐5p and mRNA encoding eukaryotic elongation factor 2 (eEF2) were detected by quantitative RT‐PCR. Moesin and eEF2 protein levels were tested by western blot assay. Dual‐luciferase reporter assay was used to examine the relationship between miR‐642a‐5p and eEF2. Cell viability was assessed using the 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide assay, and cell permeability was analyzed using the transendothelial electrical resistance assay. We report that miR‐642a‐5p levels are significantly up‐regulated in LPS‐stimulated PMVECs, and miR‐642a‐5p contributes to LPS‐induced hyperpermeability and apoptosis of PMVECs. LPS treatment results in down‐regulation of eEF2 in PMVECs. Overexpression of eEF2, a direct target of miR‐642a‐5p, inhibited the effect of LPS on PMVECs. miR‐642a‐5p promoted LPS‐induced hyperpermeability and apoptosis by targeting eEF2. Thus, miR‐642a‐5p and eEF2 may serve as potential targets for acute lung injury/acute respiratory distress syndrome diagnosis or treatment. Abstract : miR‐642a‐5p promotes lipopolysaccharide‐induced hyperpermeability and apoptosis by targeting eukaryotic elongation factor 2. Thus, miR‐642a‐5p and eukaryotic elongation factor 2 may be potential targets for acute lung injury/acute respiratory distress syndrome diagnosis or treatment.